2004
DOI: 10.1158/1078-0432.ccr-04-0378
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cells Circulate in the Peripheral Blood of All Major Carcinomas but not in Healthy Subjects or Patients With Nonmalignant Diseases

Abstract: Purpose: The purpose of this study was to determine the accuracy, precision, and linearity of the CellSearch system and evaluate the number of circulating tumor cells (CTCs) per 7.5 mL of blood in healthy subjects, patients with nonmalignant diseases, and patients with a variety of metastatic carcinomas.Experimental Design: The CellSearch system was used to enumerate CTCs in 7.5 mL of blood. Blood samples spiked with cells from tumor cell lines were used to establish analytical accuracy, reproducibility, and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

66
1,985
6
24

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,290 publications
(2,139 citation statements)
references
References 24 publications
66
1,985
6
24
Order By: Relevance
“…EpCAM is a surface marker that is widely expressed by different tumor cells and has been used to separate tumor cells in diagnostic settings for many years already. 17,23 EpCAM antibody functionalized beads were assembled using Protein A (or Protein A/G hybrid)-coated magnetic clusters with cluster diameters of 50 nm, 200 nm, 300 nm, 1 μm, and 4 μm (according to the manufacturer; Figure 1a). Transmission electron micrographs of the 300-nm clusters show a uniform size and shape of the particles (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…EpCAM is a surface marker that is widely expressed by different tumor cells and has been used to separate tumor cells in diagnostic settings for many years already. 17,23 EpCAM antibody functionalized beads were assembled using Protein A (or Protein A/G hybrid)-coated magnetic clusters with cluster diameters of 50 nm, 200 nm, 300 nm, 1 μm, and 4 μm (according to the manufacturer; Figure 1a). Transmission electron micrographs of the 300-nm clusters show a uniform size and shape of the particles (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CellSearch system relies on EpCAMs and cytokeratin for cell identification and enumeration, respectively. The CTC detection rates range from 11% to 57% in different tumors types (Allard et al, 2004). As EpCAM and cytokeratin are not expressed in a fair proportion of CTCs, this method has had to be continuously improved.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%